2007
DOI: 10.11646/zootaxa.1402.3
|View full text |Cite
|
Sign up to set email alerts
|

Four new species of Sabatieria Rouville, 1903 (Nematoda, Comesomatidae) from the Continental Slope of Atlantic Southeast

Abstract: Sabatieria is the most abundant genus along the Campos Basin, Rio de Janeiro (Brazil). Four new species of Sabatieria (Nematoda-Comesomatidae) from the Continental Slope of Atlantic Southeast are described. Sabatieria spiculata sp.nov. is characterized by the size of spicule and the presence of dorsal tooth ; S. paraspiculata sp. nov. by tail shape and the maximum diameter; S. bitumen sp. nov. by spicule shape with an arrow-like distal part and the S. subrotundicauda sp.nov. by a round tail and reflected ovary. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Details about the material and methods (field and laboratory works) and about the study area are shown in Botelho et al (2007).…”
Section: Methodsmentioning
confidence: 99%
“…Details about the material and methods (field and laboratory works) and about the study area are shown in Botelho et al (2007).…”
Section: Methodsmentioning
confidence: 99%
“…The Campos Basin is located on the continental shelf and slope of Rio de Janeiro, Brazil, between 21 ○ 30' N and 23 o 30' S. The study area, field methodology and laboratory methods were described by Botelho et al (2007). The holotypes and allotypes were deposited at the National Museum of Rio de Janeiro (MNRJ), Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…Samples from the continental slope of Campos Basin off south‐eastern Brazil recently provided important results that increased our knowledge of the biodiversity of meiofauna along the Brazilian coast, which is currently the object of intensive taxonomic and faunistic research (e.g. Botelho et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In this area, nematodes are the most abundant meiofaunal organisms, followed by harpacticoid copepods (Netto, Gallucci & Fonseca, 2005; Botelho et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%